Against Orthodoxy Social Theory and Its Discontents - Aronowitz, S. (Political Philosophy and Public Purpose, 2015)
The book contains groundbreaking and immersive essays on crucial 20th Century scholars on social theory, discussed and analyzed from a radical, critical theory perspective. Aronowitz provides his unique and lauded critical eye toward the leading thinkers of our age, crafting an immersive set of essays on radical thought.